Manual de funcionamiento, mantenimiento y aplicación pedagógica de la marmita yogurtera del Laboratorio de Investigación de Lácteos de la Carrera de Agroindustria de la Universidad Técnica de Cotopaxi. - Valladares Quille, Gladys Liliana (2022)
The purpose of this study was the creation of a manual of the operation and maintenance of the yogurt pot, that will allow students of the Agroindustry career to make correct use of it, in the generation of new knowledge and research. It is carried out from qualitative and exploratory research, applied in the collection of information on the operation, the basic principles of operation and maintenance actions to extend its useful life; followed by descriptive and explanatory research, which leads to the structuring of the manual and the development of the demonstrative practice of the use of the yogurt maker. As a result, a manual is obtained, which describes the characteristics of the kettle, the requirements for its installation, the parts of which it is constituted, the start-up depending on the heat source, the routine, preventive, predictive, and corrective maintenance that must be executed to extend the useful life of equipment, the safety measures and the demonstrative practice, in which yogurt is made from 50 L of milk, in which the sequentiality of the steps of the equipment operation is observed; the parts are identified; the placement of the agitation system that homogenizes the fluid is visualized; the inlet and outlet of steam and cold water, during the pasteurization process; the release of precipitated water, subsequent to the heat transfer from the jacket (heating or cooling medium) to the fluid; the output of the elaborated product at the end of the process; the temperature variation in heating (12 °C to 80 °C) and cooling (80 °C to 45 °C); and the incubation time that maintains a constant temperature of 45 °C for 4 hours, a period in which the lactic bacteria transform lactose into lactic acid.